2014
DOI: 10.5194/cp-10-1567-2014
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial ice sheet meltdown: orbital pacemaking and CO<sub>2</sub> effects

Abstract: Abstract.One hundred thousand years of ice sheet buildup came to a rapid end ∼ 25-10 thousand years before present (ka BP), when ice sheets receded quickly and multi-proxy reconstructed global mean surface temperatures rose by ∼ 3-5 • C. It still remains unresolved whether insolation changes due to variations of earth's tilt and orbit were sufficient to terminate glacial conditions. Using a coupled three-dimensional climate-ice sheet model, we simulate the climate and Northern Hemisphere ice sheet evolution fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 73 publications
3
61
0
1
Order By: Relevance
“…The current prevailing view mostly based on theoretical considerations and results from climate models is that the Pleistocene glacial-interglacial cycles have been caused by a combination of three forcing agents: Milankovitch orbital variations, changes in atmospheric concentrations of greenhouse gases, and a hypothesized positive icealbedo feedback [101,102]. However, recent studies have shown that orbital forcing and the ice-albedo feedback cannot explain key features of the glacial-interglacial oscillations such as the observed magnitudes of global temperature changes, the skewness of temperature response (i.e.…”
Section: Citation: Nikolov N Zeller K (2017) New Insights On the Phymentioning
confidence: 99%
“…The current prevailing view mostly based on theoretical considerations and results from climate models is that the Pleistocene glacial-interglacial cycles have been caused by a combination of three forcing agents: Milankovitch orbital variations, changes in atmospheric concentrations of greenhouse gases, and a hypothesized positive icealbedo feedback [101,102]. However, recent studies have shown that orbital forcing and the ice-albedo feedback cannot explain key features of the glacial-interglacial oscillations such as the observed magnitudes of global temperature changes, the skewness of temperature response (i.e.…”
Section: Citation: Nikolov N Zeller K (2017) New Insights On the Phymentioning
confidence: 99%
“…Although the ice sheets during the LGM were not in equilibrium (Clark et al, 2009;Heinemann et al, 2014), all simulations are forced until an equilibrium is achieved. It takes around 120 kyr with a constant climate forcing until a steady state of all ice sheets is reached.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The often prohibitive cost to run climate models over periods of several millennia has limited such attempts to use of either somewhat arbitrary methods to reduce simulation time (e.g., Herrington and Poulsen, 2011;Abe-Ouchi et al, 2013;Heinemann et al, 2014) or climate models of reduced complexity (Gallée et al, 1992;Smith et al, 2003;Charbit et al, 2007;Bonelli et al, 2009;Robinson et al, 2011;Ganopolski and Calov, 2011;Stap et al, 2014). However, in spite of their focus on numerical efficiency, the ice sheet models used in some of the latter studies rival their climate model counterparts in complexity and computational cost, which is not justified for all applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we use that M = 0 in the moment when the sun passes Φ and formulate the instantanous energy balance anlogously 25 to Eq. (6) as…”
mentioning
confidence: 99%